Type II retrocaval ureter causing hydronephrosis in a cat: case report - Albernaz, V. G. P. [UNESP]; Tasqueti, U.; Meyer, F.; Miara, L. C.; Fabris, I. A. [UNESP]; Quitzan, J. G. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
Retrocaval ureter (RU) is an abnormal embryonic development of the caudal vena cava (CVC) that leads the ureter to be entrapped dorsal to the CVC. In most cases there is no clinical impact; however, it can cause hydronephrosis. We report a rare case of type II symptomatic retrocaval ureter in a feline treated with nephroureterectomy. A 4-year-old, intact male, mixed breed cat was submitted to abdominal ultrasound and severe right hydronephrosis was diagnosed, with no signs of obstruction. We performed an exploratory celiotomy, in which a displacement of the right ureter dorsal to the CVC was observed. The animal was treated with ureteronephrectomy and recovered well. No intraluminal cause was found, and a urethral catheter could be easily inserted across the ureter length. The real clinical relevance of the RU is unknown, since it is a common find in post-mortem examination without kidney impact and, when significant, is often associated to other causes of ureteral obstructions, such as calculi and strictures. Additionally, in humans, type II RU seldom develops obstruction and hydronephrosis. In our case, due to absence of other causes of obstruction, probably mechanical compression of the CVC against the psoas muscle caused the hydronephrosis.
Keywords: circumcaval; megaureter; nephrectomy; vena cava; feline